Asymmetric synthesis of allylic sulfonamides with axially and central chirality via palladium-catalyzed of atroposelective N-allylic alkylation - Dayuan Wang; Jiayi Zong; Bowen Wang; Longwu Sun; Xiao Xiao; Huri Piao; Miaolin Ke; Fener Chen (Green Synthesis and Catalysis, 2025)
Axially chiral anilide compounds are an emerging but scarcely investigated class of stereogenic molecules with potential applications as chiral catalysts, biologically active scaffolds and functional materials. Compared to the C–C axially chiral molecules, the synthesis of axially chiral anilide compounds is a challenge owing to the lower rotation barriers. Herein, the construction of chiral allylic amine bearing axial chirality and central chirality via Pd-catalyzed atroposelective N-allylic alkylation reaction of cyclic vinyl carbonates and sulfonamides is reported. A diverse range of chiral sulfonamides bearing axial chirality and central chirality were synthesized in high yields and excellent enantioselectivities (up to 92 ​% yield and 99 ​% ee). In addition, the practical application of this protocol was also demonstrated by gram-scale synthesis and derivatives of the compound.